Digital Marketing Strategies of Modern Islamic Boarding Schools - Tamam, Badrut; Kadi, Titi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
e aim of this study is to identify the digital marketing strategies implemented by Al Azhar Balikpapan and Al Mazaya Paser and to assess their effectiveness in strengthening institutional visibility and trust. The research employed a qualitative descriptive method using a multisite design, supported by observation, in-depth interviews, and documentation. Data were collected through observations, interviews, and documentation. Involving Kiai, public relations managers, and social media administrators as primary data sources, while secondary data were obtained from institutional documents, digital content of the boarding schools, and scholarly literature relevant to digital marketing in Islamic education. Data validation was conducted through source and technique triangulation. This study employs the Miles and Huberman qualitative data analysis model, which consists of data collection, data reduction, data display, and conclusion drawing or verification. Findings reveal the formulation of a Parent-Based Digital Trust Marketing (PDTM) model grounded in the principle of khidmah, emphasizing parental trust, satisfaction, and engagement as the primary social proof. The model operates through Instagram, Facebook, YouTube, official websites, and WhatsApp, utilizing educational content, activity visuals, and authentic testimonials. The strategy enhances digital visibility, builds a modern-Islamic institutional image, and effectively reaches prospective students beyond Kalimantan. Practical applications of this study include digital marketing for Islamic education, branding in faith-based institutions, and trust-based communication strategies. The novelty of this research lies in the integration of parental trust as the core driver of digital marketing effectiveness in pesantren, producing a culturally grounded model aligned with Islamic educational values. The study concludes that optimizing parental trust significantly strengthens digital marketing performance in modern Islamic boarding schools during the ongoing digital transformation in education.